Inconsciente $.A.: a encarnação dos significantes-mestres do capital - Silva, Vinicius de Azevedo (2009)
This paper intends to reflect upon some connections between the unconscious and capitalism and to ponder over the consequences of such correspondence for the subjetct. We worked with the hypothesis of an existing homology between Marx s commodity-form and the Lacanian quotation in which the signifier introduces the subject to another signifier. We concluded, from the structural point of view, that the correspondence between the subject and the commodity is the same as that between the signifier and the capital. We saw how the commodity-form, by means of fetish, interpellates the subject, inscribing in it the signifiers of capital. We point out that commodity-form is also the form of workforce-commodity , therefore it materializes in the body and in the psyche of the subjects, possibly coming back as a symptom. Finally, we saw how ideology constitutes and gets updated in the actions. We behave as fetishists in the practice, despite what we know. By doing so, we believe. Thus, an ideological dimension that was already structurally present can be expressed